NEWLY DISCOVERED MIDDLE BRONZE AGE BURIAL COMPLEXES IN THE NORTH-EASTERN CAUCASUS - Krivoseev, Mihail Vasil'evic; Moiseev, Vladimir Ivanovic; Hazamov, Dibir-Ali Alievic; Krivoseeva, Anna Viktorovna (History, Archeology and Ethnography of the Caucasus, 2025)
This article presents a burial complex from mound 7 of the Khasavyurt 5th mounds burial ground (Northern Dagestan), excavated in 2024, and introduces it into the scholarly record. The primary interment in the mound (burial 8) contained the remains of an adult male, associated with a distinctive burial rite involving piled rocks placed over a wooden grave roof and cattle skulls placed atop of the mound. The individual was interred in a large pit, positioned in a flexed posture on his left side with the head oriented to the south. Grave goods included ceramic vessels, a 1.5-turn gold pendant, a bronze knife and awl, and a stone arrow shaft straightener. Additionally, a polished bone and horse tail vertebrae were recovered, potentially representing components of a “bunchuk,” a symbol of power. The characteristics of the burial ritual and the associated artifacts suggest the high social status of the individual in burial 8 during his lifetime. Two contemporary children’s burials (burials 5 and 6) were located outside the primary mound, with a separate mound constructed over them, covering the initial one. Both children were placed in individual graves in a flexed position on their left sides, with their heads oriented to the south. Accompanying grave goods comprised ceramic and wooden vessels, and beads. Situation 2, located beneath the secondary mound and consisting of ceramic vessels and an obsidian flake under a stone slab, is also dated to the same period. The burial complex within the mound is dated to the third quarter of the 3rd millennium BC. These findings suggest that during the Middle Bronze Age, the steppe zone of Northern Dagestan participated in the broader cultural development of the Ciscaucasian and North-Western Caspian steppes, experiencing influences from both the piedmont zone and steppe communities.